Exploring 4-7-8 Breathing for Stress Relief and Improved Quality of Life in Chronic and Degenerative Diseases: A Scoping Review - Dian Pitaloka Priasmoro; Yuni Asri; Rifzul Maulina (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Chronic and degenerative diseases have a profound effect on patients' overall well-being, often accompanied by psychological distress such as anxiety and chronic stress. While pharmacological treatments are commonly used, they may have limitations, including accessibility issues and side effects, which have prompted interest in non-pharmacological interventions. This scoping review aims to systematically map and synthesize the empirical evidence on the physiological and psychological effects of the 4-7-8 breathing technique, a structured slow-breathing method that involves inhaling for 4 seconds, holding the breath for 7 seconds, and exhaling for 8 seconds. The review adhered to PRISMA-ScR guidelines and included 15 studies published between 2013 and 2024. These studies examined diverse populations and employed various methodological approaches. The findings were categorized into five major themes: (1) the 4-7-8 technique's effectiveness in reducing stress and anxiety, (2) improvements in cardiovascular markers such as heart rate variability and blood pressure, (3) its adaptability in both clinical and community-based multimodal interventions, (4) its preventive benefits for healthy individuals, and (5) its impact on parasympathetic activity via vagal pathways, enhancing autonomic regulation and emotional stability. The technique is supported by both theoretical and empirical evidence, positioning it as an accessible, low-cost psychoregulatory intervention. The results suggest that the 4-7-8 breathing technique could play a key role in holistic nursing care, health education, and public health promotion strategies, offering a simple yet effective approach to managing stress, improving mental health, and enhancing cardiovascular health. Future studies could explore long-term benefits and its integration into more diverse health interventions.